PENGARUH REPUTASI, ETIKA, DAN SELF ESTEEM SUBORDINAT TERHADAP BUDGETARY SLACK DI BAWAH ASIMETRI INFORMASI - Tri Siwi Nugraheni; Slamet Sugiri (Journal of Indonesian Economy and Business (JIEB), 2004)
Based on agency theory, this study experimentally investigates whether budgetaryslacks are different among subordinate managers with different levels of their reputation,ethics, and self esteem under different levels of information asymmetry. Subjects consist of 101 undergraduate accounting students at University of Pembangunan Nasional,Jogjakarta. This study uses a 3 x 2 factorial design to test the levels of reputation andethics. A 3 x 3 factorial design is used to test the level of self esteem. This experimentmanipulates information asymmetry into three conditions: none, low, and high as used bySteven (2002) and uses a fixed pay plus bonus. This study predicts that subordinates withlow reputation, ethics, and self esteem tend to create higher budgetary slack than do those with high reputation, ethics, and self esteem. Results show that experimental evidence supports the prediction. Future research is recommended to use truth inducing pay scheme to explore whether results of the current study are consistent.Keywords: budgetary slack, reputation, ethics, self esteem, information asymmetry.